2017
DOI: 10.1111/jcpe.12731
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of soluble CD163 in periodontitis patients

Abstract: Our findings suggest that CD163 may be involved in the pathogenesis of periodontitis and its link with systemic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 41 publications
4
12
0
Order By: Relevance
“…In this study, when we correlated the protein and gene expression of CD163 with the demographic variables and periodontal parameters in both groups, we found that though in CP (Group I), CD163 levels did not show a positive correlation with demographic and periodontal parameters ( Table 2), however, in the CP+DM (Group II), it showed a significant positive correlation with PI (p-value 0.001), BOP (p-value 0.001), PPD (p-value 0.001), and CAL (p-value 0.001) ( Table 3). This was in accordance with the Detzen et al study, where they reported that CD163 expression in saliva and serum samples of periodontitis patients was highly correlated with periodontal parameters suggesting the relationship between CD163 levels and periodontal destruction [17]. Therefore, an increased level of CD163 in our study provides a better understanding of its role in the pathology of periodontal destruction in type II diabetes mellitus.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, when we correlated the protein and gene expression of CD163 with the demographic variables and periodontal parameters in both groups, we found that though in CP (Group I), CD163 levels did not show a positive correlation with demographic and periodontal parameters ( Table 2), however, in the CP+DM (Group II), it showed a significant positive correlation with PI (p-value 0.001), BOP (p-value 0.001), PPD (p-value 0.001), and CAL (p-value 0.001) ( Table 3). This was in accordance with the Detzen et al study, where they reported that CD163 expression in saliva and serum samples of periodontitis patients was highly correlated with periodontal parameters suggesting the relationship between CD163 levels and periodontal destruction [17]. Therefore, an increased level of CD163 in our study provides a better understanding of its role in the pathology of periodontal destruction in type II diabetes mellitus.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, sCD163 has been identified as a biomarker for the diagnosis, prognosis, and monitoring of disease progression. Reports by Detzen et al have revealed the association of CD163 in saliva with periodontitis subjects [17]. Several studies have already proven that the subgingival biofilm is a primary reservoir of pathognomonic bacteria and cytotoxic agents in established periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…A study done by Detzen et al . [ 15 ] in saliva and serum of periodontitis patients demonstrated elevated serum levels of sCD163 (720.0 ± 330.6 ng/ml) which are comparable to the serum sCD163 levels of the present study. The subdue decrease in the GCF sCD163 levels from the serum sCD163 levels may be due to the molecular weight of sCD163 (130 kDa) which is higher when compared to the most commonly found proteins in GCF which are <79 kDa.…”
Section: Discussionsupporting
confidence: 87%
“…Oral hygiene status and inflammatory status were recorded using oral hygiene index simplified (OHIS)[ 18 ] and gingival index (GI)[ 19 ] at the time of clinical examination. BoP was recorded as a dichotomous index[ 15 ] (present or absent) and was expressed in percentage of bleeding. To maintain standardization and intra-examiner reproducibility probing depth (PD), CAL was recorded by a single examiner using a UNC-15 probe.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation